Social impact of recruitment and selection strategies in fostering an inclusive onboarding process - Romana, Fernando Acabado; Gestoso, Carlos Guillen; Santos, António Mário Velindro dos (Edelweiss Applied Science and Technology, 2024)
This study evaluates the importance of recruitment and selection strategies for successful onboarding, that is, the integration of new employees. A quantitative method of a descriptive nature is adopted, with an online questionnaire used to collect data. To answer the question ‘What is the impact of the recruitment and selection process on the success of onboarding/welcoming new employees?’, we analyze three variables, explored through subthemes, to investigate and interconnect the impact between the three. This is a cross-sectional study, suitable for describing and analyzing the predominance of certain population characteristics and the relationship between different variables at a given time. Human resource management (HRM) is crucial for any organization. Over the years, HRM has evolved and gained prominence in modern organizations, ensuring social impact and enabling people’s inclusion.